The study of microbial contaminants and some physical and chemical characteristics of the bottled water circulating in Samarra city and comparing with ordinary water - Abdul_Hamid. M. hamoudi; Afrah. T Khalaf; Jwan .N. Abood (Tikrit Journal of Pure Science)
This study included examined of  the microbial and chemical content and some physical properties of bottled water manufacturers locally and circulating in the city of Samarra markets. It was counting the number of colonies of both bacteria and fungi, and measuring the pH value and electrical conductivity and suspended solids and total distress, and bio-oxygen demand as well as the study of the concentrations of each of calcium, sodium, magnesium, potassium, nitrates, iron, fluoride, chloride and sulfate. The study has shown higher microbial and chemical contamination of the majority of the samples that 36% of the studied samples free of aerobic bacteria and 90% free of bacteria of fecal and 22% free of molds and yeasts and when comparing microbial contaminants combined found that 13% of which is devoid of the three contaminated species and 87% of which contains all of these pollutants, or some of them either. when measuring the content of chemical elements and compounds, The study showed that 54% of the samples contained an increase in potassium and 16% of them contain an increase in iron while 4.5% of the them  showed an increase in fluoride when comparing polluters together [microbial and chemical] found that only one sample devoid of all pollutants studied thus deemed unfit for human consumption.